2005
DOI: 10.1055/s-2005-837575
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Development and Sesquiterpene Lactone Secretion in Capitate Glandular Trichomes of Sunflower

Abstract: The secretion of sesquiterpene lactones (STL) in capitate glandular trichomes from the anther appendages of Helianthus annuus L. (Asteraceae) was observed by light and fluorescence microscopy and HPLC analysis. Disk flowers within the sunflower capitulum showed the known ontogenetic progression from the centre to the margin. During development of the florets, the trichomes in the anther appendages secreted their metabolites into the subcuticular secretion storage space in front of the two apical cells. All sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 47 publications
6
62
0
8
Order By: Relevance
“…Trichomes in the secretory stage were manually isolated as described (16). The trichomes were collected in 200 l ice-cold RNA extraction buffer (Aurum Total RNA Isolation kit, Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trichomes in the secretory stage were manually isolated as described (16). The trichomes were collected in 200 l ice-cold RNA extraction buffer (Aurum Total RNA Isolation kit, Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…This particular sunflower cultivar has abundant trichomes on its florets (ϳ200 per floret), where a diverse array of STLs including a costunolide derivative (haageanolide, Fig. 2B) were isolated and structurally characterized (16). Importantly, the floret trichomes can be visualized by a dissecting microscope, allowing physical separation of pure trichomes by mechanical methods.…”
Section: Construction Of Cdna Library From Sunflower Capitatementioning
confidence: 99%
See 1 more Smart Citation
“…In the Asteraceae family, glandular trichomes are particularly rich in sesquiterpenoids (Seaman et al, 1980;Heinrich et al, 2002;Göpfert et al, 2005;Bertea et al, 2006). Indeed, apart from pyrethrins, pyrethrum extracts also contain a variety of sesquiterpene lactones (STLs), such as pyrethrosin (chrysanthin) (Barton and Demayo, 1957;Barton et al, 1960), chrysanin, dihydro-b-cyclopyrethrosin, chrysanolide, and b-cyclopyrethrosin (Doskotch and Elferaly, 1969;Doskotch et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to plant structures, Marley et al (2006) found a significantly lower recovery of GIN L3 from chicory compared to ryegrass swards; although many factors could be involved, their results could be partially explained by the physical barrier represented by the presence of trichomes in chicory leaves that interfere with larval migration. Glandular trichomes act as metabolic factories in different plant organs where in the case of chicory and other members of the Asteraceae family, sesquiterpene lactones are produced and secreted to a subcuticular storage space at the apex of trichomes or excreted to the plant surface (Göpfert et al, 2005). These terpenoids play an important role as deterrents to herbivory and are toxic to pathogens; therefore, they could also represent a chemical repellent to L3, restraining vertical movement.…”
Section: Discussionmentioning
confidence: 99%